Influence of Estimated Fetal Weight on Labor Management - Bushman, Elisa T.; Thompson, Norris; Gray, Meredith; Steele, Robin; Jenkins, Sheri M.; Tita, Alan T.; Harper, Lorie M. (American Journal of Perinatology, 2020)
Objective Prior studies suggest knowledge of estimated fetal weight (EFW), particularly by ultrasound (US), increases the risk for cesarean delivery. These same studies suggest that concern for macrosomia potentially alters labor management leading to increased rates of cesarean delivery. We aimed to assess if shortened labor management, as a result of suspected macrosomia (≥4,000 g), leads to an increased rate of cesarean delivery.Study Design This is a secondary analysis of a retrospective cohort study at a single tertiary center in 2015 of women with singleton pregnancies ≥36 weeks with documented EFW by US within 3 weeks or physical exam on admission. Women were excluded if an initial cervical exam was ≥6 cm or no attempt was made to labor. In addition, patients were excluded for the diagnosis of hypertension, diabetes, or prior cesarean delivery, as these comorbidities influence the use of US, labor management, and cesarean delivery independent of fetal weight. Patients were classified as EFW of ≥4,000 and <4,000 g. Secondary analysis examined the impact of US within 3 weeks of admission when compared with physical exam at the time of admission. The primary maternal outcomes were duration of labor and cesarean delivery. Duration of labor was evaluated as total time from 4 cm to delivery (with 4-cm dilation being a surrogate marker for active labor), length of time allowed from 4 cm until the first documented cervical change (or delivery), and time in second stage of labor (complete dilation to delivery). Cesarean delivery for arrest of labor was a secondary outcome. Student's t-test, Mann–Whitney U-test, chi-squared test, and Fisher's exact test were used for univariate data analysis as appropriate.Results Of 1,506 patients included, 54 (3.5%) had EFW of ≥4,000 g. Women with EFW of ≥4,000 g had a larger body mass index, higher fetal birth weight, were more likely to be undergoing induction of labor, had a more advanced gestational age, and were more likely to have had an US within 3 weeks of delivery. They were more likely to undergo cesarean delivery (29.6 vs. 9.3%, adjusted odds ratio [AOR]: 2.7, 95% confidence interval [CI]: 1.3–5.5) despite not having shortened labor times. When analyzing this population by method of obtaining EFW, those with EFW based on US rather than external palpation were more likely to undergo cesarean delivery (13.1 vs. 7.9%, AOR: 1.5, 95% CI: 1.01–2.12), again without having shortened labor times.Conclusion EFW of ≥4,000 g and use of US to estimate fetal weight do not appear to shorten labor management despite being associated with an increased risk of cesarean delivery.
Keywords: estimated fetal weight; fetal; obstetrics; labor curve; labor management